Love with Obstacles - Garcia, Dora; Akhmatova, Anna (Berlin : K. Verlag, 2020)
Love with Obstacles (Amor Rojo) brings together Spanish artist Dora Garcia’s collaborative research on the life and legacy of Alexandra Kollontai (1872–1952)—a revolutionary, socialist, feminist, activist, and intellectual. From 1922 to 1945, Kollontai was a Soviet ambassador in various countries, including Mexico. She was a key agitator for the sexual and social emancipation of women; as the only female member of the first Soviet government, she also managed to implement many measures women continue to fight for today, including the legalization of abortion and the protection of women’s rights. Already at the end of the 1920s, Kollontai’s texts had been translated into many languages, finding a special resonance in Spanish-speaking countries; her influence is still felt in contemporary Latin American feminist struggles. The book includes Alexandra Kollontai’s essay “On the ‘Dragon’ and the ‘White Bird,’” translated into English here for the first time. It is followed by a selection of poems by Anna Akhmatova, one of the most significant Russian poets of the twentieth century. In keeping with Amor Rojo’s focus on Kollontai’s legacy in Mexico and her connection to contemporary feminist movements, the book also features a rare collection of images that document women’s struggles from the Archive of the Feminist Movement (1964 to 1990), created by the editor, activist, and photographer Ana Victoria Jiménez, and the Historical Archive of the Lesbian Feminist Movement in Mexico (1976–present), founded by the lesbian feminist activist Yan María Yaoyólotl.
With texts by Anna Akhmatova, Paloma Contreras Lomas, Ruth Estévez, Dora Garcia, Alexandra Kollontai, Carla Lamoyi, Maria Lind, Rina Ortiz, Ana Sofia Rodriguez Everaert & Alvaro Ruiz Rodilla
This publication is published in conjunction with Dora Garcia's exhibition Love with Obstacles, curated by Ruth Estévez at the Rose Art Museum, Brandeis University, Waltham, Massachusetts/USA, 13 February to 17 May, 2020
boek
Keywords: Garcia, Dora; Kollontai, Alexandra